Formulation, Development and Evaluation of Mucoadhesive Tablet of Giclazide. - Malvania, Maulik. J.; R. Patel, Dr. Ravi.; Patel, Dr. L.D.; Patel, Dr. Yogesh; Raval, Mr. Anil (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Extending the residence time of a dosage form at a particular site and controlling the release of drug from the dosage form are useful especially for achieving controlled plasma level of the drug as well as improving bioavailability. The objective of this study was to extend the GI residence time of the dosage form and control the release of Gliclazide using mucoadhesive tablet to achieve controlled plasma level of the drug which is especially useful for 12 hrs. Matrix tablets of Gliclazide were formulated using different mucoadhesive polymers namely HPMC K4M, HPMC K15M and HPMC K100M, Carbopol 934. Formulations were evaluated for preformulation parameters, in vitro drug release profile and release kinetics. The formulations were found to have good preformulation characteristics. FTIR and DSC indicated the absence of any significant chemical interaction within dug and excipients. The develop mucoadhesive tablet, which is pharmaceutically equivalent and robust formulation of gliclazide by using complexation method and in this method we use microwave irradiation technique and its evaluation and also compare with kneeding method. Optimized formulation showed results near to predicted result and stability studies showed no changes in tablets after 1 month of accelerated stability studies. By using different polymers (HPMC K4M, HPMC K15M, HPMC K100M and Crbopol 934) and 32 factorial design with gliclazide in appropriate proportions matrix mucoadhesive, sustained and stable release tablets could be prepared which shoes prolonged therapeutic effect and improves patient compliance and drug efficiency.